The diagnostic evaluation model of Andalusia - Sánchez Mellado, Casto (Avances en Supervisión Educativa, 2007)
The coming in force f the Organic Act of Education implies the assumption of the basic competences as one more element in the curriculum and the recognition of their value in the permanent training of citizens. The Diagnosis Evaluation in Andalucia is reviewed in accordance with the fundamentals of the Act and the regulations in force for Diagnosis Evaluation in publicly-funded schools in this autonomous region.The Diagnosis Evaluation has got both an internal and an external character. It is internal as long as the application and the correction of examination tests are entrusted to the teachers in the school, and it is external due to the use of examinations tests provided by the education Authorities. It has also got a census character since it is applied to all and everyone of students in the 5th form of Primary education and the 3rd form of Compulsory Secondary Education in every school.